Understanding the contribution of metabolism to Mycobacterium tuberculosis drug tolerance - Samuels, Amanda N.; Wang, Erin R.; Harrison, Gregory A.; Valenta, Joy C.; Stallings, Christina L. (Frontiers in Cellular and Infection Microbiology, 2022)
Treatment of Mycobacterium tuberculosis (Mtb) infections is particularly arduous. One challenge to effectively treating tuberculosis is that drug efficacy in vivo often fails to match drug efficacy in vitro. This is due to multiple reasons, including inadequate drug concentrations reaching Mtb at the site of infection and physiological changes of Mtb in response to host derived stresses that render the bacteria more tolerant to antibiotics. To more effectively and efficiently treat tuberculosis, it is necessary to better understand the physiologic state of Mtb that promotes drug tolerance in the host. Towards this end, multiple studies have converged on bacterial central carbon metabolism as a critical contributor to Mtb drug tolerance. In this review, we present the evidence that changes in central carbon metabolism can promote drug tolerance, depending on the environment surrounding Mtb. We posit that these metabolic pathways could be potential drug targets to stymie the development of drug tolerance and enhance the efficacy of current antimicrobial therapy.